PERLINDUNGAN TERHADAP KEPENTINGAN PEREMPUAN DALAM PRAKTIK PERCERAIAN MUBARA’AH DI MASYARAKAT SASAK PULAU LOMBOK - Zulfatun Ni’mah (MUWAZAH : jurnal kajian gender, 2016)
this study aims to explore the reasons of women Sasak, preferring divorce mubara'ah rather than go through the legal procedures in courts and; mubara'ah divorce decision effectiveness in providing protection against the interests of women. The results showed that, women prefer to divorce mubara'ah Sasak village rather than litigation in court because it was easier, cheaper and faster than in court. overseas. The practice of mubara'ah be allowed to live by the government, and even tend to be protected, through the act of manipulating the data by the village government, in order that people who have divorced mubara'ah can remarry without having to show a divorce certificate from the court. The action manipulate this data, known, tolerated and accepted by the Office of Religious Affairs with the appropriate reason for divorce Islamic law. Divorce mubara'ah provides protection against the interests of women in society, related to marital status, the right to joint property and child custody. However, such protection is weak when dealing with the need of the orderly administration of the country, for example: birth certificate, family card, registration of Hajj and registration work abroad.